Naturalizing Phenomenology: A Must Have? - Albertazzi, Liliana (Frontiers in Psychology, 2018)
Quite a few cognitive scientists are working towards a naturalisation of phenomenology. Looking more closely at the relevant literature, however, the 'naturalising phenomenology' proposals show the presence of different conceptions, assumptions, and formalisms, further differentiated by different philosophical and/or scientific concerns. This paper shows that the original Husserlian stance is deeper, clearer and more advanced than most supposed contemporary improvements. The recent achievements of experimental phenomenology show how to 'naturalise' phenomenology without destroying the guiding assumptions of phenomenology. The requirements grounding the scientific explanation of subjective experience are discussed, such as the nature of the stimuli, their variables, and their manipulation by properly phenomenological methods.